Synthesis of bacterial cellulose and herbal extract for the development of wound dressing. (2019) - Pooja, R.; Vadodaria, Ketankumar; Vidhya, S.
Abstract: Bacterial cellulose (BC) has been extensively used in wound management as it has various unique features and it is biocompatible. The only disadvantage of BC is that it has poor antimicrobial property. There are various ways to modify the BC in order to optimize its antimicrobial activity and biocompatibility. Silver is already being impregnated into BC and it is widely used as wound dressing. This project highlights the properties and synthesis process of BC. The yield percentage of BC was observed to be 802.4 by using scoby culture. In addition, its physical, chemical and biological work has been evaluated with the addition of henna extract. Soxhlet extraction was used to extract the biologically active components from henna sample and a dry film of BC was made. The structural modification was analyzed using SEM. Wound scratch assay test showed that BC with henna extract in it, healed wound of up to 90% on mouse fibroblast cells (L292).